Jumping the box, the demographic trends and perspectives of non-traditional-age undergraduate students: a mixed methods approach - Nilsson, Liza (My University, 2019)
Purpose: Higher Education Institutions (HEIs) worldwide are facing increased pressure to meet the needs of non-traditional-age students (NTASs), defined here as 25 and older. However, there is not only a lack of supportive institutional cultures for NTASs who pursue a deinstitutionalised life course, but also scholarly knowledge pertaining to the trends in enrolments and perspectives of NTASs according to different socio-demographic variables. This mixed methods study addressed the need for increased social support and scholarly knowledge by comparing the changing demographic profile and perceptions of undergraduate NTASs at two South African universities: the University of the Witwatersrand (Wits) and Stellenbosch University (SU). Theory: Guided by several theoretical perspectives to abductively theorise results (participation, symbolic life course, self-determination, human capital, social identity, structural lag, involvement, and social integration), five distinct arguments are presented. Firstly, there is a lack of hypotheses development and testing in countries from Africa (amongst others) on the NTAS phenomenon which may potentially contribute towards the development of a comprehensive theory of adults’ participation in education. Secondly, from a symbolic life course perspective, it is argued that fewer undergraduate NTASs enrolled over time than had previously been the norm. Thirdly, from the perspective of self-determination theory (with reference to human capital theory), it is argued that NTASs are predominantly extrinsically motivated to enrol at university later in life, as opposed to intrinsically motivated. Fourthly, from the perspective of social identity theory, it is argued that NTASs conform to the notion of self-enhancement, which refute contrary claims in the literature. Finally, from the symbolic (deinstitutionalised) life course and structural lag perspectives, it is argued that there is lack of suitable peer- and academic support available at the institutional level to certain cohorts of NTASs, as opposed to NTASs as a whole. Methods: An adaptation of a convergent mixed methods design was employed to first conduct a systematic review of existing scholarship, published between 1994 and 2016, from three regions (Southern Africa, Australia and Northern America) on NTASs who enrolled for on-campus degree courses. Second, anonymised, student demographic data were sourced from Wits and SU. Bivariate and multivariate analysis were conducted on two purposive samples: (1) undergraduate non-traditional-age student enrolments (UNTASEs) (n=54 737) over a period of two decades (1994–2014); and (2) the total number of undergraduate student enrolments (TUSEs) (n=61 023) for two years only (1994 and 2014), utilising seven variables: year of enrolment, age, institution, gender, race, home language, and academic discipline. Third, quantitative and qualitative survey data were collected simultaneously via web-based questionnaires. A purposive sample of undergraduate NTASs who were 25 and older at the time of enrolment was selected (n=364) after data collection. Quantitative and qualitative survey data were analysed separately (bivariate and thematic analyses) across six variables (age, institution, gender, race, relationship status, and commencer/returner) to determine the extent to which undergraduate NTASs’ perspectives were similar or different. Survey results were triangulated with results from the systematic review, and linked to relevant theories, to develop three hypotheses (motivation, experience, and social support hypotheses). The two forms of data were finally mixed together during the discussion of hypotheses results. As this is a non-experimental study, no distinction is made between dependent and independent variables. Results: Over a period of two decades, the undergraduate student population at Wits and SU have not diversified with respect to age (UNTASEs’ representation decreased from 11% of TUSEs in 1994, to only 8% in 2014), but have diversified with respect to race (especially in traditional-age Africans, aged 24 and younger, whose representation increased from 14% of TUSEs in 1994, to 88% in 2014) and, to a lesser extent, gender (women’s representation increased from 45% of TUSEs in 1994, to 55% in 2014). Quantitative and quantified-qualitative survey data results suggest that respondents’ perceptions vary according to their socio-demographic classifications. Nonetheless, triangulated results suggest that NTASs as a whole tend to be primarily extrinsically motivated to enrol at university for career-related reasons, degree/qualification-related reasons and increased financial security and, to a lesser extent, intrinsically motivated for lifelong learning and self-development. These motivations are congruent with self-determination theory’s definition for integrated regulation. NTASs also tend to perceive their experiences in a predominantly positive light, which corroborates the notion of self-enhancement in social identity theory. Lastly, results suggest that there is lack of suitable peer- and academic support available to certain cohorts of undergraduate NTASs at the institutional level, indicative of a partial structural lag. Theoretical implications: This study makes an makes an original contribution towards scholarly knowledge as it elucidates the extent that undergraduate NTASs’ perceptions, regarding their motivations, experiences and social support structures, vary according to their socio-demographic classifications. To the best of my knowledge, this study is the first to utilise the symbolic life course perspective and social identity theory to understand the NTAS phenomenon. It is anticipated that the findings from the demographic analyses and hypotheses will not only contribute to cross-cultural findings based in South African HE, but also contribute towards the development of a comprehensive theory of adults’ participation in education. Practical implications: Should policy-makers consider the recommendations provided, future NTASs may potentially benefit from increased peer- and academic support, which in turn may improve their sense of relatedness and well-being.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfillment with the requirements for the degree of Doctor of Philosophy Johannesburg, 2019